2011
DOI: 10.1007/s10640-010-9444-8
|View full text |Cite
|
Sign up to set email alerts
|

Context and the VSL: Evidence from a Stated Preference Study in Italy and the Czech Republic

Abstract: SummaryWe report on the results of a survey based on conjoint choice experiments that was specifically designed to investigate the effect of context on the Value of a Statistical Life (VSL), an important input into the calculation of the mortality benefits of environmental policies that reduce premature mortality. We define "context" broadly to include i) the cause of death (respiratory illness, cancer, road traffic accident), ii) the beneficiary of the risk reduction (adult v. child), and iii) the mode of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(38 citation statements)
references
References 53 publications
3
34
1
Order By: Relevance
“…Examples are Alberini and Scasny (2010) and Alberini and Scasny (2011) who give Bbasic information^and Tsuge et al (2005). A full meta-analysis of stated preference studies (OECD 2012) did not find evidence to suggest a cancer premium, instead recognising that the morbidity preceding fatality generates a higher value for cancer risk reductions, but recommending that morbidity costs prior to death should be added separately as opposed to being incorporated in a cancer premium.…”
Section: Context Latency and Cancer Risksmentioning
confidence: 99%
“…Examples are Alberini and Scasny (2010) and Alberini and Scasny (2011) who give Bbasic information^and Tsuge et al (2005). A full meta-analysis of stated preference studies (OECD 2012) did not find evidence to suggest a cancer premium, instead recognising that the morbidity preceding fatality generates a higher value for cancer risk reductions, but recommending that morbidity costs prior to death should be added separately as opposed to being incorporated in a cancer premium.…”
Section: Context Latency and Cancer Risksmentioning
confidence: 99%
“…Other studies have used the multi-attribute design of CE to examine the effect of context on respondents' WTP (Tsuge, Kishimoto et al 2005, Alberini andŠcasný 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the responses to our valuation questions are consistent with economic theory and "scope" requirements (Corso et al, 2001;Hammitt and Graham, 1999). 11 However, the coefficients on pain and quality-of-life indicators are estimated imprecisely, are from earlier studies at the same locales (Alberini and Ščasný, 2011). The VSCC is somewhat 11 Briefly, the responses meet the "scope" requirement if the WTP is proportional to the size of the risk reduction, which means there is a single VSL.…”
Section: Resultsmentioning
confidence: 99%
“…Jones-Lee et al, 1985;Mendeloff and Kaplan, 1989;McDaniels et al, 1992;Savage, 1993;Tolley et al, 1994;Magat et al, 1996;Van Houtven et al, 2008). Stated-preference valuation studies have found either i) little evidence that the cancer VSL is higher than the VSL for other causes of death (Hammitt and Liu, 2004;Hammitt and Haninger, 2010;Chestnut et al, 2012), ii) modest cancer "discounts" (Tsuge et al, 2005, andAdamowicz et al, 2011), or iii) large variations associated with different causes of death (cancer, respiratory disease, road traffic accidents), resulting in cancer premia of 90-156% (Alberini and Ščasný, 2011;. A metaanalysis by OECD (2012) concludes that there seems to be no systematic cancer premium, and notes that in benefit-cost analyses morbidity costs prior to death should be added to the mortality benefits.…”
Section: Introductionmentioning
confidence: 99%